Environmental Risk Assessment of Genetically Modified Organisms, Volume 3. Methodologies for Transgenic Fish 2007
DOI: 10.1079/9781845932961.0061
|View full text |Cite
|
Sign up to set email alerts
|

Development of transgenic fish: scientific background.

Abstract: This chapter highlights some of the important examples of transgenic fish development. An overview of important steps in fish transgenesis is given. The status of development in the case of transgenic carp, tilapias, Atlantic salmon and mud loach is discussed. Other future applications of transgenic fish are presented. The key research and capacity needs for further development of transgenic fish are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
1
12
1
Order By: Relevance
“…Therefore, of the 1,800 microinjected embryos, 657 hatched and 453 of these larvae survived until yolk sac absorption was complete. This decreased viability of microinjected embryos has been reported by numerous studies, and the present scores were generally in agreement with those previously reported (Nam et al, 2007). In total, 441 individuals were viable at 1 month post-hatching and 435 individuals survived to 50 days of age, which was not significantly different from the viability of non-injected groups during the same period (P > 0.05).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Therefore, of the 1,800 microinjected embryos, 657 hatched and 453 of these larvae survived until yolk sac absorption was complete. This decreased viability of microinjected embryos has been reported by numerous studies, and the present scores were generally in agreement with those previously reported (Nam et al, 2007). In total, 441 individuals were viable at 1 month post-hatching and 435 individuals survived to 50 days of age, which was not significantly different from the viability of non-injected groups during the same period (P > 0.05).…”
Section: Resultssupporting
confidence: 82%
“…Conversely, the occurrence of PCR-negative fish in the large-sized group could be explained by either a mosaic distribution of the transgene across tissues or an extremely high level of mosaicism in the fin tissues that were chosen for PCR screening. Genetic mosaics are often reported to result from microinjected embryos (Nam et al, 2007).…”
Section: Generation Of Autotransgenic Common Carp and Early Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although functional characterization of the 5 0 -flanking upstream regions has been made only in several fish species, it is generally agreed that b-actin promoter has the broad functional potential to drive the constitutive expression of downstream foreign genes in fish cells and tissues (Takagi et al 1994;Noh et al 2003;Hwang et al 2003;Brooks et al 2007;Er-meng et al 2010). The potential utility of the fish b-actin regulator has been successfully demonstrated by previous attempts to generate transgenic fish strains acquiring desired traits such as growth stimulation and disease-resistance (Nam et al 2001(Nam et al , 2007Lin et al 2010), to improve the efficacy of DNA vaccination in fish (Ruiz et al 2008) and also to develop a siRNA-based tool for therapeutic treatment against fish viral diseases (Zenke et al 2010).…”
Section: Introductionmentioning
confidence: 95%
“…In addition, the transgenic manipulation of aquaculture fish species using gene(s) related to quantitative traits has received attention due to its potential as a powerful tool in the molecular genetic breeding of farmed fishes for productivity enhancement (Nam et al, 2001(Nam et al, , 2007. The microinjection of DNA into fertilized eggs has long been utilized to produce transgenic fish strains, although novel methodologies to induce homologous and/or targeted transgenesis have been challenged recently in some fish models (Rembold et al, 2006;Grabher and Wittbrodt, 2007;Casco-Robles et al, 2010).…”
Section: Introductionmentioning
confidence: 99%